A new genus and species of the aphid parasitoids (Hymenoptera: Braconidae: Aphidiinae) from Baltic amber - Davidian, Elena M.; Manukyan, Andranik R.; Belokobylskij, Sergey A. (Zootaxa, 2022)
A new genus and species, of aphid parasitoid, Protoctonus groehni Davidian, gen. et sp. nov. (Braconidae: Aphidiinae), are described from Late Eocene Baltic amber. This new genus is similar to fossil genera Protacanthoides Mackauer, 1961, Promonoctonia Starý, 1973 and Sakhalinoctonus Davidian, 2021, as well as with extant Calaphidius Mackauer, 1961, Falciconus Mackauer, 1959 and Aclitus Foerster, 1862. The new genus differs from aforementioned ones by having fewer antennomeres, and in elements of fore wing venation, propodeum areolation, and shape and setosity of the ovipositor sheath.